Clinical Presentation of American Tegumentary Leishmaniasis in a Leishmania (Viannia) braziliensis Endemic Hotspot: A 35-Year History - Almazán, María Cristina (2023)
American tegumentary leishmaniasis (ATL) is a neglected tropical disease affecting the skin and mucosa. American tegumentary leishmaniasis due to Leishmania (Viannia) braziliensis is endemic in Argentina, where the Department of Oran is a hyperendemic focus. All cases of ATL with laboratory confirmation evaluated at a referral center in Oran city between 1985 and 2019 were analyzed retrospectively. Information from cases included clinical form, lesion size and number, time of evolution, and anatomical location; sex, age, and geographic origin were also studied. The temporal distribution of cases was analyzed. A total of 3,573 cases were included in the analysis. The ratio of males to females was 3:1 and the median age was 33 years old. Eighty-seven percent of cases were from Oran city and its surroundings, highlighting the hyperendemic nature of the area. Regarding clinical forms, 92.5% of cases were cutaneous and 7.5% were mucosal, with a median evolution time until clinical evaluation of 30 days and 7 months, respectively. Single cutaneous lesions were more frequent, localized mainly on the exposed areas in the upper and lower limbs. Secondary events were observed and described in 140 (4%) cases, with a median interval of 3.8 years for the appearance of recurrent mucosal disease in previously cutaneous forms. This is the largest case series of ATL due to L. (V.) braziliensis. The most classic presentation is of adult males with single cutaneous ulcers in exposed body areas, with, 10% of cases with mucosal complications. This comprehensive clinical characterization serves as a basis for future studies of the care and control of this neglected tropical disease.